Methodological Issues in Management Research - Mishra, Sambit Kumar (Ushus Journal of Business Management, 2007)
In order to produce information that will be dependably useful to managers, research must be carefully planned, carried out, and interpreted, Good research does not just happen. It is the result of deliberate application of well-tested methods. The aim of this paper is to outline some of those methods and why they are important.